A Test of Executive Behavior in the Local Public Sector - Santerre, Rexford E. (The Review of Economics and Statistics, 1990)
This paper provides an empirical framework to test three competing theories regarding the behavior of public executives in the local public sector. These alternative theo- ries are the public interest, median-voter and expense preference (or surplus-maximizing Leviathan) models. This study tests these various theories by determining whether aggregate property values, the median-value of housing or administra- tive expenditures is a more significant determinant of the salary of a representative school executive in Connecticut. The empirical results lend some support for the expense preference model (Leviathan model) of public executive be- havior.